Optimization strategy of Small and Medium Enterprise (SMEs) products of Bintan Regency - Setyadiharja, Rendra; A. Karim, Zamzami; Siam, Nurbaiti Usman; Budimand, Shahril; Arfa, Desmayeti; Rianto, Faizal (2020)
There are some products from Bintan Regency SMEs that already have loyal consumers in a number of countries. However, SMEs are still faced with trading rules in the export sector. This is the main problem. In addition, there are problems with people's unstable purchasing, and a broad marketing reach separated from island to island. The purpose of this research was to establish a marketing optimization strategy for SMEs products in Bintan Regency. The research method used in this study is the Mix-Method approach. With a total sample of 65 SMEs using a random sampling cluster sampling technique and also purposive sampling. By using SWOT analysis, this research produces several strategies in SMEs marketing products that are obtained based on quantitative and qualitative analysis, namely Strengthening SMEs Institutions and Human Resources, Establishing SMEs Communities, Developing Business Partnerships, and Utilizing Information Technology in Developing Marketing SMEs Products.